The Power of Images – Coin Portraits of Roman Emperors on Jewellery Pendants in Early Southeast Asia - Borell, Brigitte (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
This contribution presents fi nds of jewellery pendants with imitations of Roman coins from Southeast Asia. The examples from Óc Eo in southern Vietnam have been known already since the 1940s. The state of our knowledge has now been broadened by the fi nds from U Thong and Khlong Thom in Thailand. In some cases, the great faithfulness of the imitations permits an exact identification of the original prototype. The fi nd of a mould leads to the conclusion of local production. The custom of wearing Roman coins or their imitations as pendants is documented by numerous finds from southern India. The equivalent phenomenon in Southeast Asia is to be seen in the context of the network of maritime routes. In the early centuries after the turn of the era, their connections extended from the South China Sea to the Mediterranean. Questions arise regarding the reception and meaning of the depictions on these jewellery pendants in their respective Eastern environment. The article will be available as a PDF in the near future.